Reforming Elementary Education and Skill Development in India - Subodh Kumar (Journal of Commerce and Trade, 2018)
A nationwide sub-programme under the Sarva Shiksha Abhiyan, “Padhe Bharat Badhe Bharat” was launched in August, 2014 to improve language development by creating an enduring interest in reading and writing with comprehension, and to create a natural and positive interest in mathematics related to their physical and social world. Various steps have been taken by the States and UTs under this initiative by creating supplementary learning material and reading corners, providing activity kits etc. for children in early grades. According to World Bank, about 13 million people enter the working age every year but only 3 million new jobs are created every year. The demographic advantage being predominantly in the rural areas, the need of the hour is to improve the skill set of the labour force such that they are productively engaged in the job roles emerging from Digital India, rural rood connectivity, development of smart cites, expressways, Swachh Bharat-Grameen etc.